A Critical Review of the Chapter Five of The Languages and Linguistics of Western Asia: An Areal Perspective Entitled: “The Caspian Region and South Azerbaijan: Caspian and Tatic” - Saeedreza Yousefi; Mahinnaz Mirdehghan Farashah (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this research is to introduce and present a critical review of the chapter entitled “The Caspian region and south Azerbaijan: Caspian and Tatic”, by Donald L. Stilo. Formally, his research is encased into a book as a full chapter, including 10 sections. In theory and methodology, this research is based on areal linguistics and areal typology, respectively. The research investigates the geographical, lexical, grammatical, and phonological characteristics of Caspian and Tati, two North Western Iranian (NWI) language families, which are spoken in the south and west of the Caspian sea region. In addition to these two groups, Stilo introduces a new group called ‘Tatoids’, which includes Rudbari and Taleqani. According to Stilo, this special status for this recent type is that these two varieties were originally Tatic which, under the intense influences of Caspian and Persian, have lost all their Tatic grammatical structures. New findings of this research are the introduction of Tatoid language group and the determination of the linguistic isoglosses of Tatic and Caspian language groups which are located almost on the geographical borders among Iran and its northern neighbors.